PENINGKATAN HASIL BELAJAR IPA SISWA MELALUI MODEL PEMBELAJARAN CTL (CONTEXTUAL THEACING AND LEARNING) DI KELAS V A SDN 021 TANJUNG PALAS - Jenny ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low result belaja fifth grade science students at SDN 021Tanjung Palas, out of 25 students only 8 students (32.00%), rendahnnya learning outcomes iscaused by: (a) students lack enthusiasm in learning; (b) students are not able to answerquestions that are of reason; (c) teachers do not involve students actively in learning; (d) lessthan the maximum in using props; and (e) the level of students' understanding of the subjectmatter IPA is still low. This research is a classroom action research (PTK), this study aims todescribe the results of learning through the use of learning model CTL. The subjects werestudents of class V A 021 SDN Tanjung Palas. This study was conducted by two cycles.Improved learning outcomes in terms of four categories, namely absorption, the effectivenessof learning, mastery learning completeness students both individual and classicalcompleteness and thoroughness of learning outcomes. The instrument used for data collectionis an oral test and a written test in the form of worksheets that do after the learning process.The results showed that the learning outcomes of science students has increased at eachcycle, as shown by the acquisition of mastery learning students, the first cycle the number ofstudents who pass are 15 students or 60% and the second cycle the number of students whopass are 22 students or 88% , It can be concluded that through CTL learning model canimprove learning outcomes a fifth grade science students at SDN 021 Tanjung Palas.